Effect of regular consumption of provitamin a biofortified staple crops on vitamin a status in populations in low-income countries - Haskell, M.; Tanumihardjo, S.A.; Palmer, A.; Melse-Boonstra, Alida; Talsma, Elise F.; Burri, B. (Rural Outreach Program, 2017)
Biofortification of staple crops with provitamin A (PVA) carotenoids is an innovative strategy for controlling vitamin A (VA) deficiency in low-income countries (LIC). Plant breeding programs have been successful in developing biofortified varieties of cassava, maize, and orange-fleshed sweet potatoes that contain amounts of PVA-carotenoids that have the potential to impact VA status in human populations. Nutrition studies indicate that beta-carotene in biofortified staple crops is converted efficiently to VA in the body. Randomized, controlled, community-based efficacy and effectiveness trials have been conducted to assess the effect of regular consumption of PVA-carotenoid biofortified staple crops on VA status. Results indicate that regular consumption of biofortified staple crops increases plasma beta-carotene concentrations consistently, but has a moderate effect, or no effect, on VA status, when assessed by serum retinol concentration, breast milk retinol concentration, or total body VA stores. Studies are currently underway to further investigate whether consumption of biofortified staple crops improves VA status in population subgroups at risk of VA deficiency, and to better understand how to optimize the biological impact of these interventions in resource-poor settings.